AI in the Classroom: A rapid evaluation of AI-generated lesson plans in Islamabad’s public schools - Aslam, Nawaz; Qureshi, Ghada; Hassan, Syed Mustafa (EdTech Hub, 2025)
This report presents a rapid evaluation of AI-generated lesson plans currently being used in public schools in rural and urban Islamabad under the National Institute of Excellence in Teacher Education (NIETE). These centrally developed, scripted lesson plans are aligned with the national curriculum and built on the Gradual Release of Responsibility (GRR) model, with additional elements of the 5E and Inquiry-Based Learning (IBL) models in science, and the Concrete-Pictorial-Abstract (CPA) model in maths. Using a mixed-methods approach—including teacher surveys, focus group discussions, key informant interviews, and an expert rubric-based review—the study assesses the lesson plans' quality, relevance, and adaptability. Teachers expressed strong support for the lesson plans, especially in terms of reduced workload and structured delivery, though concerns were raised around flexibility, contextual responsiveness, and teacher agency. While the study does not evaluate student learning outcomes, it provides actionable insights and recommendations for improving the design, support, and implementation of AI-generated instructional tools, particularly as the programme scales to other provinces in Pakistan, such as Balochistan. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Equity and Agency in Technology-Supported Teacher Professional Development in Tanzania: Research Instruments Pack - Chachage, Kristeen; Hennessy, Sara; Koomar, Saalim; Swai, Calvin; Massam, Winston; Jacob, Winnie; Anthony, Gervace; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Mwakabungu, Fika; Mrosso, Vicky; et al. (EdTech Hub, 2025)
This pack contains links to research instruments developed by EdTech Hub, the University of Dodoma, Aga Khan University, and Tanzania Institute of Education for the second phase of a study investigating the scale-up and local contextualisation of a national technology-supported teacher professional development programme known as MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, which translates as ‘teacher continuous professional development’ [TCPD] in English). The instruments draw on previously published research instruments used in Phase 1 of our research, plus examples from other sources that exemplify best practices in education research. We are making these tools available to other researchers and practitioners and hope that they will prove useful. They are provided in editable format so that others can modify them as they see fit. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Sierra Leone Digital Learning Landscape Analysis: Developing the National Digital Learning Strategy - Waziri, Nafisa; Mufti, Abdal; Ramesh Vasudevan, Sharanya; Beoku-Betts, Iman; Oyedele, Oluwatomisin (EdTech Hub, 2025)
In 2024, the World Bank submitted a request to EdTech Hub's Helpdesk to support the Government of Sierra Leone in developing a National Digital Learning Strategy. The Hub initiated the process with the creation of this digital learning landscape analysis. The report identifies achievements and progress to date, as well as key challenges and priority areas going forward. It is based on primary and secondary data collection methods, including key informant interviews, focus group discussions, and a comprehensive desk review. Other relevant sources to gain insight into existing EdTech initiatives, interventions, and challenges within the country were also reviewed. Keywords: EdTech; National Digital Learning Strategy; landscape analysis; Ministry of Basic and Senior Secondary Education; Teaching Service Commission. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

From algorithm outputs to classroom impact: A conversation with Marian Abu, director of teacher management at the Teaching Service Commission - Frazer, Madleen Madina (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _EdTechHub_Output; _r:AddedByMyEducationEvidence

EdTech for Special Educational Needs and Disabilities in Malawi: Setting the Research Agenda - Plaut, Daniel; Pitchford, Nicola; Humphrey, Catherine (2024)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

TCPD in Tanzania: Phase 2 Round 1 Recommendations - Swai, Calvin; Chachage, Kristeen; Koomar, Saalim; Hennessy, Sara; Massam, Winston; Komba, Aneth; Mwakabungu, Fika; Paskali, Jonathan Hegwa; Anthony, Gervace; Mrope, Winifrida Jacob; Malibichi, Mustapha; Mutura, Emmanuel; et al. (EdTech Hub, 2024)
The study reported here is for Phase 2 of the research project known as ‘The Impact of a Tech-Supported, School-Based Teacher Continuous Professional Development Model on Learning Outcomes in Tanzania’ and part of the global Empowering Teachers Initiative (ETI), which comprises 10 country projects. It is closely aligned with the implementation of ‘MEWAKA’ (Mafunzo Endelevu kwa Walimu Kazini) or Teacher continuous professional development (TCPD), and the Tanzania National TCPD implementation plan. MEWAKA is an innovative, school-based, technology-supported programme currently being implemented by the Government of Tanzania in schools nationwide. The research was co-developed and designed collaboratively between EdTech Hub, the Tanzania Institute of Education (TIE), and Aga Khan University, with consultation from key stakeholders at the ministry level. The work’s current (second) phase focuses on issues of equity, agency, and adaptation in scaling MEWAKA. This policy brief summarises the key findings and recommendations from the first round of data collection for Phase 2 of the research project, conducted in March 2024. Keywords: teachers; teacher professional development; Tanzania; MEWAKA; participatory research An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech in Lao People's Democratic Republic: A Rapid Scan - Afzal, Nimra; Thang, Sarah; Tulivuori, Jukka; Thinley, Sangay; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive. Nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, and in this case, Lao People’s Democratic Republic (PDR). This report was originally written in February 2024. It is based primarily on desk research, with quality assurance provided by a country expert based at the Australian Council for Educational Research. Keywords: Ministry of Education and Sports; digital skills; training programmes; government expenditure; learning outcomes; disparities An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Remote Supervision Options for School Quality Assurance Officers: Recommendations for a cost-effective and rapid develop-and-test process - Beoku-Betts, Iman; Ampofo, Rudolph; Haßler, Björn (EdTech Hub, 2024)
The Sierra Leone Secondary Education Improvement Programme II (SSEIP II) is a five-year programme funded by the UK Foreign, Commonwealth and Development Office (FCDO) to support the Ministry of Basic and Senior Secondary Education (MBSSE) to improve learning outcomes for students at secondary level and to increase the enrolment, retention and well-being of girls and children with disabilities in school. Part of the programme includes exploring the use of different digital tools for School Quality Assurance Officers (SQAOs), including tools for remote visits. In December 2022, the EdTech Hub collaborated with the Government of Sierra Leone and implementing partners of the Leh Wi Lan programme (continued under SSEIP II) to better understand what factors affect the variability in the activity levels of SQAOs and the level of engagement with digital tools by school principals. Based on the findings of this research, the SSEIP II project will look at supporting the MBSSE to formalise remote supervision options for the SQAOs, particularly for those with remote clusters. As part of this work, this report focuses on recommendations for how SQAOs can conduct remote school visits, particularly for schools in hard-to-reach areas.An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

TCPD in Tanzania: Design-Based Implementation Research Cycle 2 Recommendations - Chachage, Kristeen; Koomar, Saalim; Swai, Calvin; Massam, Winston; Hennessy, Sara; Masonda, Jonathan Paskali; Anthony, Gervace; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Mtenzi, Frederick; Komba, Aneth; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or teacher continuous professional development [TCPD]) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The research project, 'The Impact of a Tech-Supported, School-Based TPD Model on Learning Outcomes in Tanzania, using Design-Based Implementation Research (DBIR)', closely aligns with the Tanzania National TCPD implementation plan, to evaluate the implementation of MEWAKA at school level. This policy brief presents a summary of the key findings and recommendations from the second cycle of the DBIR carried out between September and November 2023. Keywords: TCPD; teacher professional development; design-based implementation research; primary education; Tanzania; communities of learningAn output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech in Vietnam: A Rapid Scan - Honda, Delanie; Halla, Ken; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Vietnam. This report was originally written in March 2024. It is based primarily on desk research, with quality assurance provided by country experts at Southeast Asian Ministers of Education Organization (SEAMEO) centres. Keywords: out-of-school children and youth; digital education; Southeast Asia; girls’ education; secondary education An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

How Can Participatory Methods Centre Teachers Within Education Policy? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the potential for participatory methods to bring teachers closer to the decision-making table. Insights from those closest to the work shed light on the daily contextual realities that can determine the mechanisms for optimal success or failure of a programme. However, these voices are often neglected in the design, implementation, and evaluation of interventions. We examine why and how teachers can have a voice and a space to share their wisdom to inform and improve education policy. We draw on EdTech Hub's work across various low- and middle-income contexts to offer practical insights when using or planning to use participatory methods. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt about the methods used and how they have contributed to ensuring teachers’ voices are heard at the policymaking level. We also explore areas that require further research, noting five issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to participatory methods for centring teachers in education policy. Keywords: teacher; participatory methods; action research; implementation research; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

What is 'Nudging' and How Does it Change Behaviour in Education? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the behaviour change strategy of leveraging concise messages at strategic decision points (i.e., ‘nudging’) to influence the behaviour of a recipient towards a desired outcome. We focus on EdTech Hub’s work concerning nudge messaging. It builds on work from messaging interventions in Ghana and Kenya, linking these to the broader literature on the topic. It emphasises that although there is a strong and growing evidence base for nudge technologies, effective implementation remains dependent upon context-specific adaptation. It is not inevitable that nudge messaging interventions will lead to positive outcomes — indeed, outcomes are often mixed. It is therefore vital to understand the specific impacts of interventions on particular groups of recipients. We present findings and recommendations that should inform how nudging technologies in education are approached and what decision-makers need to consider in order to ensure uptake and minimise risks. Lastly, we explore areas that require further research, namely, the changing nature of nudging due to artificial intelligence, the safeguarding risks of nudging, persisting questions about cost-effectiveness, and how nudging can more specifically target learning. Keywords: Behavioural psychology; EdTech; education; messaging; nudging; participation An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Cognitive and Learning Disabilities: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Afzal, Nimra (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with cognitive and learning disabilities. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. We discuss the nature of EdTech for learners living with cognitive and learning disabilities, the effectiveness of these initiatives, and barriers for accessing EdTech. The RER aims neither to advocate nor discourage the use of technology to support education for learners with coginitive and learning disabilities, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; cognitive disabilities; learning disabilities; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; ⛔ No INSPIRE recid found

Cohort Learning Handbook - Nicholson, Bryony (EdTech Hub, 2024)
The Cohort Learning Handbook captures EdTech Hub’s approach to building cohorts on its Evidence-Led Entrepreneurship Course. The course aims to help entrepreneurs adopt and utilise evidence to learn and to scale their products and services. The Handbook is for individuals and organisations who support EdTech entrepreneurs (e.g., accelerators, entrepreneurship programmes, and funders). Building a cohort supports entrepreneurs to learn quickly and more confidently as a result of learning with, from, and alongside peers sharing the same experience. By ensuring that the learning journey is the most effective it can be, we ensure our work has the greatest impact. By facilitating a cohort journey for EdTech entrepreneurs, you can: - Leverage the unique power of a cohort to improve the learning experience and learning outcomes. - Diversify the support on offer. - Streamline and improve technical support that we often offer ventures. The handbook includes a list of resources and templates for you to use and covers a range of topics and practical suggestions from key principles and onboarding to graduation and supporting alumni. Keywords: cohort; community; learning; collective; incubators; accelerators An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Working Towards Education Success Using Data: A review of Ghana's journey towards improved learning outcomes using data - Radford, Kate; Ampofo, Rudolph (EdTech Hub, 2024)
The sub-Saharan Africa region is trapped in a learning crisis with devastating implications for children. The Covid-19 pandemic further exacerbated the situation, with children losing an estimated equivalent of an additional year’s learning. Not addressing the regional learning crisis will have a detrimental impact on economic development and well-being and risks restricting future national and regional economic growth and productivity and fuelling social unrest. Education research has shown that good quality education system data, when judiciously used, can support improved learning outcomes among a host of other positive impacts on national education systems. This case study is the first in a series documenting the journey of Ghana’s Ministry of Education towards the effective use of data to guide its decision-making for policy and practice. Keywords: data for decision making; data governance; data management; Ghana; education data systems; evidence-based policy An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Understanding Teacher School Choice Preferences: What Matters Most for Teacher Deployment in Sierra Leone? (EdTech Hub Preprint, 2023)
This exploratory mixed-methods study investigates the factors that shape where teachers want to work in Sierra Leone. We identify five dominant factors: monetary incentives, school conditions, opportunities for professional development and support, school location, and relationships with the school and the community. Importantly, these factors combine to push and pull teachers to different locations. Moreover, the factors interact with individual teacher characteristics such as gender, family status, and experience to influence school choice preferences. This set of factors — and their interaction with certain teacher characteristics — continues to shape preferences as teachers move up the career ladder. Keywords: Teacher deployment, teacher preferences, Sierra Leone, teacher supply, remote schools An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

School-to-School Mobility Patterns and Retention Rates of Payroll Teachers in Sierra Leone - Espinoza-Revollo, Patricia; Ali, Yusuf; Garrod, Oliver; Atherton, Paul; Mackintosh, Alisdair; Ramirez, Ana; Beoku-Betts, Iman; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone. Recent studies from this series have shown that being put on the government payroll can incentivise teachers to relocate to remote areas of the country. There is a concern, however, that being put on the payroll does not necessarily ensure the retention of teachers in these areas and that teachers will soon move to locations they consider more favourable. As there is no data on teacher mobility patterns and schools’ teacher retention rates, policies tend to be based on anecdotal evidence. This paper aims to fill this evidence gap by exploring teachers’ school-to-school mobility trends and retention rates using the Annual School Census (ASC) data from 2015 to 2021. Using data on teachers’ individual characteristics, as well as geospatial location data of each school, the paper explores whether mobility patterns vary by teachers’ gender or qualifications and whether the teaching workforce is urbanising. While studies have looked at teacher retention, this study is the first in a low-income country to use school census data to create a panel dataset to study teachers’ movements and school retention rates over time. Keywords: teacher mobility; teacher retention rates; mobility patterns; teacher deployment; Sierra Leone; education An output of the EdTech Hub https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Telephone Survey: Caregivers' and Learners' Perspectives on SMS for Education in Kenya - Myers, Christina; Jordan, Katy; Khagame, Phoebe; Mumbi, Albina; Njuguna, Lydia; Zhao, Annette (EdTech Hub, 2022)
This document presents the structure and questions used for a telephone survey which was undertaken with a sample of learners who use the M-Shule platform and their caregivers, in Kenya, during July and August 2022. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Using technology to improve the equity of teacher allocation in Sierra Leone: the challenge and a way forward - McBurnie, Chris; Vijil, Alejandra; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

The Impact of GIS-Supported Teacher Allocation in Sierra Leone - EdTech Hub; Education Commission; Fab Inc. (EdTech Hub, 2022)
Keywords: HLR3; _r:AddedByZotZen

Design-Based Implementation Research Baseline Data Collection: Technical report - Koomar, Saalim; Adam, Taskeen; Massam, Winston Edward; Anthony, Gervace; Mrope, Winifrida Jacob; Mtenzi, Fredrick; Mwakabungu, Fika; Komba, Aneth; Hennessy, Sara; Barretto, Johnpaul (EdTech Hub, 2022)
This research study aims to investigate the effectiveness, cost-effectiveness, and sustainability of a tech-supported, decentralised, and school-based teacher continuous professional development (TCPD) model, to improve learning outcomes in rural Tanzanian primary schools. The research will test and iteratively improve the national TCPD model and roll-out (including the semi-structured Communities of Learning), as outlined in the Tanzanian National TCPD Implementation Plan (2021). We seek to understand the model’s effectiveness and the role that technology can play. The research team includes researchers from EdTech Hub, Aga Khan University, and the Tanzania Institute of Education. The study employs a Design-Based Implementation Research (DBIR) approach in the first phase and an experimental study in the second phase. Keywords: teacher professional development; EdTech; design-based implementation research; Tanzania; Community of Learning; school-based An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech That Reaches Marginalised Learners: Relevant Examples for the Indonesian Context - Rui, Yang (Tingting); Upadhyay, Arjun (EdTech Hub, 2022)
This curated list of resources presents a sample of education technology programmes that effectively reach marginalised learners, including children with SEND, girls, and children in frontier, outermost, and disadvantaged regions. This list provides short summaries of lessons in using EdTech such as radio, television, and mobile phones to reach marginalised learners, emphasising interventions and evidence relevant to the Indonesian context. Keywords: marginalised learners, Indonesia, radio, television, mobile phones, girls, no-tech options An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Understanding Barriers to Girls’ Access and Use of EdTech in Kenya During Covid-19 - Tembey, Lara; Baier, Jasmin; Ogolla, Concilia; Mohan, Prithika (EdTech Hub and Busara Center for Behavioural Economics, 2021)
The Covid-19 pandemic resulted in the closure of approximately 90,000 schools across Kenya, causing over 18 million pre-primary, primary, and secondary school learners to be out of school throughout 2020. These lockdown measures of Covid-19 are expected to amplify gender inequalities in education and girls’ access to school, with girls likely to have experienced losses in learning during the pandemic to a greater extent than their male counterparts (⇡Malala Fund, 2020). To enable continued learning during this period, numerous education technology (EdTech) solutions and products have been developed to enable remote learning. This technology can be a powerful tool for girls. Studies have shown that girls engage more than boys when provided with the same level of access to technology, and receive more benefits beyond the realm of formal education such as an increase in access to economic opportunities and a greater ability to make informed decisions about their own health (⇡Webb et al., 2020). However, social inequalities, norms and technological constraints can disproportionately prevent girls from accessing and benefiting from EdTech (⇡Crompton et al., 2021). As such, EdTech interventions and products need to be designed and implemented prioritising gender considerations, otherwise they risk increasing the digital gender divide both in terms of access and use of digital technologies and the internet and the development of skills needed to use digital technologies (⇡Kuroda et al., 2019). Our qualitative and quantitative research looked at how access and usage of learning content and edutainment through smartphone and low-tech (such as radio, Interactive Voice Response, TV) EdTech solutions can be optimised to ensure inclusivity of girls, in particular, focusing on the caregiver as the gatekeeper for access to EdTech resources. In terms of access, our research found that caregivers are primarily concerned about financial resources, books and tutors, and often do not consider using EdTech to access educational resources when they are looking for support for their children. Further, our research showed that digital literacy, caregiver involvement, norms about technology for education, and intention are the most promising levers to improve access and use of educational material. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Sierra Leone Series: Plan International and the importance of community support for distance teacher professional development programmes - McBurnie, Chris; Saidu, Arthur; Rincon Casado, Eusebio; Shergill, Maggie (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen

Sierra Leone Series: the Pikin-to-Pikin Movement and its focus on child protection, education, nutrition and health - McBurnie, Chris; Swaray, Abdulai; Kamara, Bai (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen

Sierra Leone series: Plan International and the importance of community support for distance teacher professional development programmes - Saidu, Arthur; Casado, Eusebio Rincon; Shergill, Maggie; McBurnie, Chris (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector.  In week four, we met with Arthur Saidu, Eusebio Rincon Casado and Maggie Shergill from…
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

Sierra Leone series: Freetown Teachers College and its multimodal approach to teacher professional development - McBurnie, Chris; Moriba, Sambo; Brainard, Prince (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector.  In week two, we connected with Dr Samba Moriba and Prince Brainard from Freetown Teachers…
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodoETH; dode_eth-src-eth

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Expert Consultation: Radio-Based Education in the Philippines - McBurnie, Chris (EdTech Hub, 2020)
These slides present an overview of educational radio programming with a particular focus on quality assurance and content design.
Keywords: C:Philippines; F: Helpdesk response; H:Radio; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v2; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

EdTech in Liberia: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Liberia; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

EdTech in Senegal: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Senegal; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; pu

Designing Teacher Learning Circles for Improved Foundational Numeracy Outcomes: Findings from the National Numeracy Programme in Malawi - Correa de Oliveira, André; Plaut, Daniel; Kanyoza, Charity; Boilo, Violet; Chidothi, Emmanuel; Kadzamira, Esme; Mpoola, Dorothy; McBurnie, Chris; Phiri, Magret; Haßler, Björn (EdTech Hub, 2024)
The Malawi National Numeracy Programme (NNP) was designed in 2020 in partnership with the Malawi Ministry of Education and Cambridge Education (Mott McDonald), funded by the UK Foreign, Commonwealth and Development Office (FCDO). Building on findings from a prior qualitative review of the NNP's programme components, EdTech Hub proposed a new phase of design-based implementation research (DBIR) to be undertaken in Term 2 of the 2022–2023 school year to refine the school-based teacher continuous professional development (TCPD) model of the NNP. As part of the research, EdTech Hub developed a new TLC guide to be tested in schools. Through observations, focus group discussions, and interviews, the Hub gathered teacher feedback and used it to co-design and iterate on this guide alongside teachers. This report summarises the principal findings from the study. It also outlines the research background, methodology, findings, and recommendations for the programme moving forward. Keywords: teacher continuous professional development, teacher learning circles, National Numeracy Programme (NNP), Malawi, design-based implementation research An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

MEWAKA National Teacher Development Reform in Tanzania: Design-Based Implementation Research: Cycle 1 Findings - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, G.; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fred; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teacher Continuous Professional Development [TCPD]) is a landmark, school-based teacher professional development programme being implemented nationally by the Government of Tanzania, with the ultimate aim of raising learning outcomes in schools. EdTech Hub, Aga Khan University, and the Tanzania Institute of Education (TIE) are conducting research to iteratively enhance the MEWAKA implementation at primary school level and to understand the role that technology can play in scaling TCPD. This report presents the findings and recommendations from the first cycle of design-based implementation research (DBIR) conducted in rural schools in the Lindi region. Following a pilot peer facilitator workshop, data was collected through observation and self-reporting methods between September and December 2022. The aims were to capture stakeholders' perspectives at all levels of the education system and to see how schools are implementing the programme on the ground. The emerging findings and recommendations are being used to inform the redesign and further implementation of this TCPD model, and were used to identify key areas to test and investigate in the second cycle of the DBIR in 2023. Keywords: teacher professional development; design-based implementation research; Tanzania; primary education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
Keywords: _r:AddedByZotZen

Teacher Retention and Mobility in Sierra Leone: What factors motivate teachers to stay at or leave schools? - Lurvink, Anne-Fleur; Mansaray, Kabiru; Kamara, Josephine; Khanu, Alimamy James; Cameron, Emma; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
The current study is the third in a series of research studies, which aim to generate evidence that can support the MBSSE and TSC with their teacher allocation and deployment strategy. Our first study investigated teacher preferences for school choice and uncovered important considerations for teacher deployment. Following this, we investigated mobility patterns for teachers who are on the government payroll, and payroll teacher retention rates. The latter study helped us understand where teachers move to when they change schools, and also helped us identify areas with high (hot spots) and low retention rates (cold spots). The current study is explanatory in nature and aims to understand why teachers stay at or leave their schools. Keyword: teacher allocation; teacher retention; teacher mobility; Sierra Leone An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech for Ugandan girls: Affordances of different technologies for girls' secondary education during the Covid-19 pandemic - Damani, Kalifa; Daltry, Rebecca; Jordan, Katy; Hills, Libby; Evans, Laura (Development Policy Review, 2022)
Motivation This article discusses the use of educational technology (EdTech) in girls' education at PEAS (Promoting Education in African Schools) schools in rural Uganda during the Covid-19-related school closures. Purpose This article addresses a research gap surrounding the potential use of EdTech to support girls' education, focusing on the barriers to girls' EdTech use and how technology might be used to enhance girls' education in disadvantaged rural areas—specifically their academic learning and their social and emotional learning. Methods and approach A sequential, explanatory mixed-methods case-study approach was used. Quantitative exploration of a dataset of 483 Ugandan students, from 28 PEAS schools, was first conducted, followed by interviews with PEAS staff to elucidate the reasons and context behind the findings. Findings Findings show that female students are less likely than male students to have access to their caregivers' phones for learning. The form of EdTech that appeared to be most beneficial for girls' academic learning was radio; girls also had significantly more interest in tuning into radio broadcasts than boys did. Also, poorer boys were more likely to be influenced by SMS messages than wealthier boys. Apart from gender-based differences, students with more highly educated parents found SMS messages more helpful, and phone calls from teachers appeared to help boost younger students' self-confidence. Policy implications The findings suggest that policy-makers need to: carefully consider provision of education through multiple modes of EdTech in order to ensure that it reaches all students; ensure that caregivers are involved in the strategies developed for girls' education; make EdTech interventions interactive; and consider language in EdTech interventions. Given the gender differences which emerged, the findings are of relevance both to supporting the continuation of educational provision during periods of school closure, and also in terms of finding additional ways to support girls' education alongside formal schooling.
Keywords: Covid-19; EdTech; education; gender; rural Uganda

2021 Annual School Census Final Report - Ministry of Basic and Senior Secondary Education, Sierra Leone (2022)

Republic of Sierra Leone Settlement Extents - GRID3 (Center for International Earth Science Information Network (CIESIN), Columbia University and Novel-T, 2021)

Education Sector Analysis. Assessing the enabling environment for gender equality - Republic of Sierra Leone (UNICEF, IIEP - UNESCO, 2020)

Sierra Leone’s Medium-Term National Development Plan 2019-2023: Education for Development. - Government of Sierra Leone (2019)